Fragments and Coherence: Celebrity Femininities in Cover Story of Kartini Magazine - Aquarini Priyatna (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2017)
This paper discusses the notion of femininity values assigned to women and considered to be the sign of womanhood. More specifically, it discusses the representation of female celebrity femininity as staged in their auto/biographical practice in women’s magazines Kartini. The paper also analyses how celebrity auto/biographical practices constitute what can be considered as feminine narrative [structure] that is fragmented yet coherent. Focusing on the issues of time and space, I argue that autobiographical practice in print media such as women’s magazines, despite its popular terrain, displays a complex structure of fragments and coherence in representing female celebrities as both public persona and private persons. Likewise, the alternative form of auto/biographical practices appearing in women’s magazines suggest that more embracing critical accounts of contemporary auto/biographical practices are necessary.